Raman Laser Polymerization of C60 Nanowhiskers. (14th March 2012) - Kato, Ryoei; Miyazawa, Kun'ichi
Abstract : Photopolymerization of C 60 nanowhiskers (C 60 NWs) was investigated by using a Raman spectrometer in air at room temperature, since the polymerized C 60 NWs are expected to exhibit a high mechanical strength and a thermal stability. Short C 60 NWs with a mean length of 4.4 μ m were synthesized by LLIP method (liquid-liquid interfacial precipitation method). The A g (2) peak of C 60 NWs shifted to the lower wavenumbers with increasing the laser beam energy dose, and an energy dose more than about 1520 J/mm 2 was found necessary to obtain the photopolymerized C 60 NWs. However, excessive energy doses at high-power densities increased the sample temperature and lead to the thermal decomposition of polymerized C 60 molecules.